Development of a measurement scale of strategic consensus on pedagogic teams - Puente-Palacios, Katia (2013)
Strategic consensus is a group process that can be described as the agreement among team members on strategic matters for success at work. The psychometric evidences of the validity of an assessment scale measuring strategic consensus in pedagogic teams are analyzed. Participants were 140 school teachers in Quito (Ecuador). Statistical analyses of the applied scale containing 14 items revealed a uni-dimensional factor structure explaining 49.7% of the variance. The internal consistency of the scale was satisfactory (? = .92; r item-total = .66). Results show that the scale is an useful tool for the diagnosis of the existence of consent among members of pedagogic teams and contributes to a full understanding of the phenomenon.